The United States’ Hegemonic Influence in International Law: A Case Study of the ICC’s Probe into Israel’s War Crimes - Devi, Murtanti Fajarrani; Maulida, Zahratul; Purwana, Veronica Cynthia Putri; Rasmitha, Nadia Risa (Media Hukum Indonesia (MHI), 2025)
The International Criminal Court (ICC) was established to uphold accountability for the most serious crimes such as genocide, war crimes, and crimes against humanity through the principle of complementarity. However, this idealism often clashes with global political dynamics, especially when dealing with superpowers. This study examines the practice of United States hegemony over the ICC through sanctions policies, specifically the implementation of Executive Order 13928 targeting ICC officials related to the investigation of war crimes in Afghanistan and Palestine. Using a qualitative approach based on literature studies, the study finds that the United States' sanctions policy is a form of unilateral coercion and a manifestation of American exceptionalism that strengthens the politics of impunity. These sanctions not only threaten the independence of the ICC apparatus but also have a domino effect on the ICC's legitimacy, authority, and ability to carry out its mandate effectively. These findings indicate that international justice mechanisms remain vulnerable to geopolitical intervention, necessitating the strengthening of legal structures and international cooperation to ensure the ICC can operate without political pressure from powerful states.